Bortezomib for the treatment of mantle cell lymphoma: an update. (August 2016) - Hambley, Bryan; Caimi, Paolo F.; William, Basem M.
Bortezomib is a first in class proteasome inhibitor, initially approved by the US Food and Drug Administration for the treatment of plasma cell myeloma. Bortezomib has been approved for the treatment of relapsed and refractory mantle cell lymphoma (MCL) and, more recently, in the upfront setting as well. Treatment algorithms for MCL have rapidly evolved over the past two decades, and the optimal regimen remains to be defined. The choice of treatment regimen is based on disease risk stratification models, the expected toxicity of antineoplastic agents, the perceived patient ability to tolerate the planned treatments and the availability of novel agents. As new drugs with novel mechanisms of action and variable toxicity profiles come into use, treatment decisions for a given patient have become increasingly complex. This article provides an overview of the evolving use of bortezomib in the rapidly changing management landscape of MCL